2000
DOI: 10.1515/znc-2000-7-810
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones from Centaurea achaia, a Greek Endemic Species: Antifungal Activity

Abstract: The aerial parts of Centaurea achaia afforded, in addition to several known sesquiterpene lactones and sesquiterpene hydroxyesters, a new germacranolide and a new elemanolide. Their structures were determined as the 8a-0-(4,5-dihydroxy-tigloyloxy) esters of salonitenolide and of 11,13-dihydromelitensin, respectively. The in vitro antifungal activity of most compounds was tested against nine fungal species using the micro-dilution method. All the tested compounds showed strong antifungal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 5 publications
7
33
0
2
Order By: Relevance
“…Elemane-type sesquiterpenes have also been isolated from C. chilensis (Negrete et al, 1993), C. paui (Cardona et al, 1997), C. cuneifolia (Aslan and Oksuz, 1999), C. achaia (Skaltsa et al, 2000b) and C. aspera (Marco et al, 2005). Our investigation demonstrated that elemane-type metabolites are the main sesquiterpenes in C. hierapolitana which is a member of Phalolepis section.…”
Section: Resultssupporting
confidence: 58%
“…Elemane-type sesquiterpenes have also been isolated from C. chilensis (Negrete et al, 1993), C. paui (Cardona et al, 1997), C. cuneifolia (Aslan and Oksuz, 1999), C. achaia (Skaltsa et al, 2000b) and C. aspera (Marco et al, 2005). Our investigation demonstrated that elemane-type metabolites are the main sesquiterpenes in C. hierapolitana which is a member of Phalolepis section.…”
Section: Resultssupporting
confidence: 58%
“…However, it should be noted that low polarity is one of the molecular requirements suggested for the antifungal activity of sesquiterpene lactones [25,28,33]. As it is observed from the reported tables of MICs and MFCs values [16][17][18], among the studied compounds, germacranolides which have retention times on a RP-18 column higher than the other groups are the most active. This supports the hypothesis of an inverse relationship between polarity and antifungal activity for sesquiterpene lactones.…”
Section: Resultsmentioning
confidence: 76%
“…Continuing our study on sesquiterpene lactones, in a first step we attempted to predict the pharmacokinetic properties of an interesting data set of potent antifungal sesquiterpene lactones, isolated from Greek taxa of Centaurea sp., by projection on the pre-calculated ADME models developed in VolSurf [16][17][18]. In a second step, we tried to optimize the pharmacokinetic properties of data set's selected molecules by ADME in silico screening of a semi-synthetic derivatives virtual library.…”
Section: Introductionmentioning
confidence: 99%
“…All the compounds tested showed great antifungal activity comparable and sometimes better than miconazole used as control (Skaltsa et al, 2000a;.…”
Section: Amberboa Lippiimentioning
confidence: 93%